Education, interaction and language: educational possibilities in the context of teaching-learning in the Portuguese Language (Research, Society and Development, 2022)
In the school context, especially in the Portuguese Language discipline, it is identified the problematization of still having lectures of an expository character, which follow an inductive plan: to theorize about a given content, disregarding that the teacher develops a work with the student based on the tripod education-interaction-language. Given the above, this article aims to present didactic possibilities for the teaching of Portuguese language, in order to provide, more specifically, reflections on the way to work grammar in the context of teaching-learning. Methodologically, it starts from a qualitative approach, resorting to the use of bibliographic research. To this end, the study was based on the Sociodiscursive Interactionism postulated by Bronckart (1999). The results demonstrate the effectiveness of practicing grammar through interactionist activities and the need to promote reflective discussions about pedagogical actions that favor the teaching task. It is concluded that Sociodiscursive Interactionism is a founding tool to operate as a support to teachers who aim to develop, in an interactive way, Portuguese Language classes in Basic Education, particularly in Elementary II.